The Influence of Financial Knowledge, Parental Financial Socialization, and Fear of Missing Out (FOMO) on The Financial Behavior of Gen Z students in Indonesia : Examining The Moderating Role of Gender - Azizah, Afifatun Nur; Susilaningsih, Susilaningsih; Noviani, Leny (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to examine the role of gender in moderating the influence between financial knowledge, parental financial socialization, and FoMO on the financial behavior of Gen Z students in Indonesia.This research method uses a quantitative approach with a descriptive design that focuses on the statistical analysis of numerical data. The population of this study was students from the 2020 and 2021 intakes who were registered in the economics study program of the Faculty of Teacher Training and Education at Sebelas Maret University. The sampling technique employed combines probability sampling and proportionate random sampling. A total of 224 students participated in data collection, which involved distributing a Google Forms link and the questionnaire via messaging applications (such as WhatsApp) and social network chat features. IBM SPSS 26 software was used to analyze the data using Moderated Regression Analysis (MRA). The study's findings indicate financial behavior is influenced by financial knowledge, parental financial socialization, and FoMO (p<0.05). Additionally, while financial knowledge and FoMO are not moderated by gender (p>0.05), parental financial socialization's effect on financial behavior is moderated by gender (p<0.05). The implications of this study highlight the importance of integrating financial literacy into university education, using a more practical and technology-based approach. Lecturers are encouraged to design learning that not only focuses on theory but also involves financial simulations and technology to help students better understand financial concepts interactively. In addition, universities should offer training programs or financial literacy workshops to equip students with better financial skills.